DIMENSIONAL STABILITY AND TENSILE STRENGTH OF WOOD PLASTIC COMPOSITE FORMED WITH HIGHER PLASTIC CONTENT - Lawal, K. J.; Oluyege, A.; Bola, T. S.; Aina, K. S.; Falemara, B. C.; Gakenou, O. F. (FUDMA JOURNAL OF SCIENCES, 2020)
This study investigated the dimensional stability and strength properties of plastic bonded composites produced from wood waste particles and polyethylene using extruder. The composites were produced from wood species such as such as: Triplochiton scleroxylon, Terminalia superba and Gmelina arborea at a mixing proportion of 60:40 (plastic/wood) on a weight by weight basis. Evaluation of properties was carried out in accordance with the American Standard Testing Methods of 570 and 790 to determine the dimensional stability and strength properties of the composites. The results of findings revealed that water absorption and thickness swelling of the wood composites ranged from 10.08% to 15.36% and 4.33% to 5.58% respectively after 24hours and 48hours immersion in water. Tensile strength also ranged between 29.4MPa and 45.6MPa. Composite board made from T. superba wood particles had the lowest significant water absorption (10.08%), thickness swelling (4.33%) and highest significant tensile strength (45.6MPa) compared to composites produced from G. arborea and T. scleroxylon wood particles. It was observed that high density wood species exhibit lower water intake, lower thickness swelling and higher tensile strength, while the contrary is the case for lower density wood species. In conclusion, the three tree species used for the study could be recommended for the production of wood composite like particle board, fibre board, wood cement boards and others.